The Archaeology of Watercraft Abandonment
XIII, 375 p.
Keywords: The historical importance and archaeological potential of deliberately discarded watercraft has not been a major feature of maritime archaeological enquiry. While research on the topic has appeared since the 1970s as books, chapters, and articles of limited focus and distribution, most examples take the form of unpublished archaeological reports and graduate theses. Additionally, there is no existing single source that represents the great diversity of geographical, historic, thematic, and theoretical contexts of ship graveyard sites and deliberately abandoned vessels. In contrast with much of the theoretical or case-specific literature on the theme of watercraft discard, this volume communicates to the reader the common heritage and global themes that ship graveyard sites represent. It serves as an illustration of how the remains of abandoned vessels in ship graveyards are sites of considerable research value. Moreover, the case studies in this volume assist researchers in understanding the evolution of maritime technologies, economies, and societies. The Archaeology of Watercraft Abandonment is intended to expose research potential, create discussion, and reinforce the significance of a prevalent cultural resource that is often overlooked.